Seismic attribute feasibility study for fault and fracture analysis and integration with spectral decomposition: Application in Sarawak basin - Hamidi, R. (International Petroleum Technology Conference (IPTC), 2019)
Fault and fracture study has a great importance in hydrocarbon prospect exploration and development. Consequently, there have been lots of efforts to analyze the existence and extent of faults in subsurface layers using different methods and tools available to geoscientists; among which the seismic attributes have been proven to be efficient in detecting areas affected by faults and fractures. Seismic attributes help interpreters to highlight details focusing on the geological features of interest in seismic data. However, there are some limitations in the performance of these tools, as the algorithms are dependent on the seismic survey parameters, quality of the data and its existing patterns, and geology of the study area. Consequently, new strategies and algorithms are needed to improve the information obtained from the calculated attributes. In this study, fault and fracture damage zone analysis is done on three - dimensional seismic data from Sarawak basin in Malaysia. Commonly used seismic attributes to detect such features including variance, dip - magnitude, curvature, and gradient - magnitude are applied. Next, spectral analysis, as a tool to identify events with different frequency content is used which can detect the patterns related to faulting and fracturing of the subsurface layers. The proposed method in this work is to examine the attributes' performance on spectrally decomposed seismic cubes to unmask the details present at different frequencies. Accordingly, the seismic attributes are applied on the selected cubes, and the color blended cubes of the outputs are evaluated. As the results show, the new strategy reveals more detailed information that already exist in seismic data but cannot be distinguished because they are concealed in the full band seismic cube. Comparing each pair of conventional vs. spectral assisted attributes shows enhancement of the results (more details and better resolution) in all evaluated seismic attributes with the proposed method. Â© 2019, International Petroleum Technology Conference